(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2015)
The present study was carried out to assess the existing status of compost usage on vegetable production and determine the overall effect of household waste compost (HWC) on growth and yield of vegetables and enhancement of soil fertility in the monga areas of Bangladesh. A field survey was conducted on 152 sampled farmers during 2010 to 2011. Questionnaire containing both closed and open-ended questions were used to assess existing production practices of vegetables using compost in both homestead and field conditions. Three field trials at Badargonj and Kawnia upazilas of Rangpur district were conducted taking four treatments i.e. control, recommended doses (RD) of fertilizers, HWC at the rate of 10 tha-1, and HWC 10 t ha-1 plus RD as IPNS based with Lal shak, Palong shak, Pui shak and Tomato. Base line survey results indicated inadequate knowledge of the farmers on use and preparation of the household waste compost. Yield data of all vegetables i.e. Tomato, Lal shak, Palong shak and Pui shak indicated that the combined application of nutrients using organic and inorganic sources were significantly better than that of solitary application of inorganic fertilizers. The potential of household waste compost applied @ 10 t ha-1 along with inorganic fertilizers applied was found highly satisfactory in producing Tomato, where yield was recorded 75 t ha-1 in the study area. The fresh yield of Palong shak was found 16 t ha-1 when recommended doses of inorganic fertilizers were applied, but it was about 19 t ha-1 under combined application of HWC @ 10 t ha-1 and inorganic fertilizers following IPNS concept. The fresh yield of Pui shak was found about 49 t ha-1 under combined application of organic and inorganic nutrients. Considering the availability and costs of different composts, it is evinced that HWC contained good amount of NPK which indicates its potentiality to be used as a soil amendment, improving soil fertility and crop productivity. It can be an alternative to chemical fertilizer to increase soil microbial populations and enzyme activities and to promote the soil nutrient for horticultural crops in the unfertile areas especially in the monga areas of Bangladesh. DOI: http://dx.doi.org/10.3329/ijarit.v4i2.22640 Int. J. Agril. Res. Innov. & Tech. 4 (2): 22-28, December, 2014